Computer games, trust, and immediacy: Role-playing as immigrants in the South - Bouchillon, Brandon C.; Stewart, Patrick A. (Computers in human behavior, 2023)
Trust in racial and ethnic diversity has been decreasing in America for the better part of a century. The present study replicated a games-based approach to establishing trust in immigrants during COVID-19. Students in an online American National Government class created a fictional persona from either Mexico, India, or China, and sought U.S. citizenship. A posttest-only control group design was analyzed during Fall 2021 and Spring 2022. Subjects who played the game had significantly higher levels of trust in immigrants. They trusted immigrants from China, India, and the Middle East at higher levels than the control group did as well. Immediacy also interacted with role-playing group, such that applying for citizenship as Chinese immigrants had the largest effect on trusting when the experience was perceived as realistic, immersive, and engaging. Pretending to be less visible immigrant groups appears to generalize trust to immigrants from everywhere at high levels of immediacy. •This study replicates a past experiment, this time using a control group.•Playing a game where characters apply for citizenship leads to trusting immigrants.•Playing as larger, more visible groups leads to trusting immigrants in general.•When playing as less visible groups, immediacy is important for trusting.•Realism, immersion, and engagement can be used to facilitate trust when gaming.